PERKEMBANGAN KAJIAN TEORITIS DAN TIPOLOGI TAFSIR DI MESIR - Muhammad Mudzakkir (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
The development of interpretation from time to time has a long history and different styles and has its own characteristics so that it reaches its shape as we can see today. Egypt is one of the countries that has become a reference in terms of scholarship, including the study of interpretation after the collapse of Baghdad. This paper uses library research using descriptive analysis methods to uncover and describe the formation of interpretations, the methods used in interpretation and to find a typology of interpretation. By preodic If we group the development of interpretation from the beginning of Islam to the modern era, especially in the area of ​​Egypt, we can divide it into three periodicals; compilation, classification, and updating. From these three stages of process, various interpretations emerge and develop over time; in the early phase of the study of interpretation, it was still oriented to the riwâyah aspect which was oriented to the interpretation of Abdullah bin Abbas; then in the next phase, namely the development stage of interpretation, it has begun to elaborate on the riwâyah aspect with dirâyah which makes language studies the main focus and in the third phase is the renewal of the study of interpretation so that perspectives emerge through more objective methods and become a reference for any social problems that plague the Ummah. Islam. This is where the development of the next interpretation begins.